The immunopathological crosstalk of diabetic periodontitis: Single-cell insights into monocyte dysregulation - Chenli Si; Xinlei Wu; Huijuan Cheng; Wentao Jiang; Huijiao Yan (PLoS ONE, 2026)
Periodontitis (PD) and type 2 diabetes mellitus (DM) are bidirectionally associated through shared chronic inflammatory mechanisms. Although monocytes serve as central immune mediators in both pathologies, their functional heterogeneity and dynamic alterations in diabetic periodontitis (PDDM) remain poorly characterized. Utilizing single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) from healthy controls, PD patients, and PDDM subjects, we systematically investigated the immunopathological crosstalk between these comorbidities. Our analysis revealed a significant shift in monocyte subpopulations, with PDDM patients exhibiting increased classical monocytes (CD14++CD16−) and decreased nonclassical monocytes (CD14 + CD16++) compared to PD counterparts. Functional profiling demonstrated PDDM-enriched classical monocytes upregulated oxygen transport pathways while suppressing chemotaxis and cytokine responses, whereas nonclassical monocytes showed impaired oxidative phosphorylation and nucleotide biosynthesis. Cell communication analysis identified reduced activity of TGF-β signaling and enhanced CCL pathway activation, collectively promoting chronic inflammation and tissue destruction. Regulatory network reconstruction revealed transcription factors (PBX1, TAL1, IRF9) governing monocyte differentiation defects and hyperinflammatory phenotypes. These results suggest mechanistic links how diabetic conditions exacerbate periodontal inflammation through monocyte reprogramming and signaling pathway dysregulation, providing a cellular roadmap for developing targeted immunotherapies in PDDM management.